Pengaruh Kualitas Pelayanan Terhadap Tingkat Kepuasan Pelanggan (Studi Pada PT Pegadaian (Persero) Pegadaian Unit Pelayanan Cabang Labuan) - Berthanila, Rethorika (Sawala : Jurnal Administrasi Negara, 2017)
The influence of service quality on customer satisfaction (Study at  PT Pegadaian (Pesero) Pegadaian Unit Service Branch Labuan)  Rethorika Berthanila. This study aims to examine the influence of service quality on customer satisfaction (Study at PT Pegadaian (Pesero) Pegadaian Unit Pelayanan Cabang Labuan).  This research is quantitative, while the population and samples taken as many as 50 customers with the accidental sampling. Research instrument data using three types of tools, namely questionnaires using Likers scale model. The questionnaire was prepared with the construction of various theories of data analysis performed at the 95% level the result is significantly along the existing hypothesis. So the results of this study told that the variable quality of service can affect satisfaction in PT. Pegadaian (Persero) Pegadain Unit Service Branch Labuan.